New petrified calamitaleans from the Permian of the Parnaiba Basin, central-north Brazil. Part I - Neregato, Rodrigo [UNESP]; Roessler, Ronny; Rohn, Rosemarie [UNESP]; Noll, Robert (Elsevier B.V., 2015)
New sphenophyte stems from the Permian of the Parnaiba Basin (central-north Brazil) are described in detail and assigned to Arthropitys, a genus that was recognised from the Euramerican and Cathaysian floristic provinces. The fossil material is reported from the Permian Motuca Formation in northern Tocantins and was discovered in fluvial deposits, which originated under seasonal conditions in a widely distributed alluvial plain environment. The silica-petrified specimens are three-dimensionally preserved and provide considerable information on histological and developmental details not previously observed in the genus. The stems show very regular branch traces, attached branches or basal branching stumps. Based on their anatomical and morphological characteristics two new species are described: Arthropitys isoramis sp. nov. and Arthropitys iannuzzii sp. nov. One specimen of A. isoramis sp. nov. shows several woody roots attached to the basal region of the stem. This record differs radically from traditional and largely generalised reconstructions of calamitaleans, which are largely understood as rhizomatous trees based on inferences with extant Equisetum. The new sizable finds underline the high potential of northern Tocantins as a widely extended fossil lagerstatte that significantly enlarges our understanding of extinct low-latitude Southern Hemisphere floral communities. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Arthropitys; Stem anatomy; Root; Parnaiba basin; Motuca formation; Permian